(2x+1)(x-2)a^2-ab(1+x^2)+(1+x)(1-x)b^2=0 将a,b视为未知 即[ (2x+1)a+(1+x)b]*[(x-2)a+(1-x)b]=0 那么x=-(a+b)/(2a+b)或者x=(b-2a)/(b-a)
解方程:(2x-3x-2)a+(1-x)b-ab(1+x)=0
1个回答
相关问题
-
解方程(1)2-x/(x-3)+3=2/(3-x) (2)a+b/x-b/a-a/b=2(ab≠0,a+b≠0)
-
1、解方程:(x-5)^-(x+4)^=0 2、设方程:x^+2(1+a)x+(3a^+4ab+b^+2)=0有实数根,
-
解关于x的方程:b(a+x)-a=(2b+1)x+ab(a≠0).
-
解关于x的方程:b(a+x)-a=(2b+1)x+ab(a≠0).
-
解方程 x²-(2a-3b)x+(a²-3ab+2b²)=0
-
解下列关于x的方程.(1)a²(x-2)-3a=x+1(2)ax+b-(3x+2ab)/3=1/2(3)(x-
-
解下列关于x或y的方程解方程:b^2x^2+2x^2-1=0;(2a-1)x=2(x-1);b^2x^2+21=3(b≠
-
下列方程①[2/x+1+3x−1=6x2−1];②[x−b/a]=2-[x−a/b](ab≠0);③[x−1/2−y+2
-
解关于x的方程:(a+2x)/a-1/b=(b+2)x/ab+1(b≠2)
-
解下列关于x的方程:(1)a2(x-2)-3a=x+1;(2)ax+b-[3x+2ab/3=12](3)[x−b/a=2